Study of the kinetics of wear of steels from the point of view of the provisions of the adhesive-hydrodynamic theory of wear - Poberezhnyi, M.M.; Kaplun, P.V.; Kolenov, S.O. (Problems of Tribology, 2022)
The article is devoted to the study of wear resistance of the surface layer of steels 40X and ШX15, when rubbed in oil I-20. A comparison of the surface layer of samples of raw and nitrided steels, before and after the tests. The study of the fine microstructure of the samples with the help of the LDFP microscope, allowed us to conclude that the samples that were subjected to ionic nitriding, improved roughness. In turn, increased the area of linear contact, reduced contact load. The graphic dependence of roughness indicators is constructed. After testing, we can conclude that nitrided steel has a long service life, namely high hardness, resistance to abrasion, durability and corrosion resistance. The mechanism for obtaining increased resources needs further study